PENGETAHUAN IBU MENYUSUI TENTANG CARA PENINGKATAN PRODUKSI ASI DI KLIMIK LMT SIREGAR - Asima Sirait; Mestika lumbantoruan; Idaria R Sidabukke (JOMIS (Journal of Midwifery Science), 2022)
With the many benefits of breastfeeding that all children get exclusive breastfeeding from newborns to 6 months of age. several factors for the failure of exclusive breastfeeding, namely the low knowledge of mothers about exclusive breastfeeding and efforts to increase exclusive breastfeeding. This study is a quantitative study with a descriptive design that aims to explore the level of knowledge of breastfeeding mothers about how to increase milk production. The population in this study were all breastfeeding mothers who came to visit the LMT Siregar Clinic with an accidental sampling technique of 38 people. The results showed that the majority of respondents had less knowledge about how to increase breast milk production (66%). It is necessary to carry out health education or similar assistance to pregnant women in the third trimester, postpartum mothers and breastfeeding mothers in an effort to increase breast milk production so that exclusive breastfeeding coverage is met..